Does a change in immigration affect the unemployment rate in host countries? Evidence from Australia - Mostafa E. AboElsoud; Anas AlQudah; Eman Elish (Journal of Applied Economics, 2020)
This study examines and evaluates the dynamic causality relationship between immigration, unemployment, wages and GDP per capita in host countries with a focus on Australia. Previous research has indicated that the economic impact of immigration is significant; nonetheless, its effect on the labour market being positive or negative is inconclusive. This study uses a Vector Error Correction Model (VECM) to examine the dynamic short- and long-run nexus between these variables in Australia over the period 1980-2016. The paper provides clear evidence to policy makers on the positive spillover effect of immigration policies developed by the Australian government.
Keywords: 330; Australia; economic growth; GDP; Immigration; unemployment; VECM; wages